A comparative study of anthropometric and physical profiles of male junior rowers, kayakers and canoers - Tamoghni Manna, A. S. (Medicina Sportiva, 2018)
Rowing, canoeing and kayaking are the very popular water-sports which involve both skill and power. Several investigators stresses on the anthropometric and physical characteristics of the players for achieving success at the international level. However, in this regard, there is a paucity of knowledge for making any comparison of these three closely related sports. Aim. The objective of the present study is to evaluate various physical and anthropometrical parameters of Indian junior male rowers, kayakers and canoers and also to explore the differences among them. Material and Method. The present study was conducted on 17 male rowers (n = 17, age = 16.2 ±1.51 years), 15 male kayakers (n = 15, age = 17.0 ±3.99 years) and 9 male kayakers (n=9, age = 15.1±0.53) respectively. Various physical and body anthropometrical parameters were measured using standard methods. Results. The height of male kayakers was found to be significantly higher than that of canoeists (p= 0.035). The arm span of rowers was found to be significantly higher than that of kayakers (p=0.007). The ectomorphic element and forearm length of rowers were found to be significantly higher than canoers (p=0.003) and (p=0.001).The trunk flexibility of rowers was found to be significantly higher than canoeists (p=0.014). Conclusions. The findings of the current study can be useful in talent identification and new induction while planning the training programs.